Robust diversity-combining receiver for wireless communications - Chen, Yanru (Nanyang Technological University, 2020)
The development of wireless communication technology is changing the way we live. In the real-life communication applications, there are always various interference sources that affect the communication quality, hence, the reliability of wireless communication is particularly important in the design of communication system. In this project, the Bit Error Rate (BER) in both Additive White Gaussian Noise (AWGN) channel and Rayleigh fading channel will be simulated and analysed by using MATLAB. This proves that fading leads to the increase of BER and affect the normal reception of the signals. One of the diversity-combining technique, Maximal-Ratio Combining (MRC) is also simulated under the M-ary Frequency Shift Keying (MFSK) and shown how it eases the fading effects.